2021
DOI: 10.26618/exposure.v10i2.6048
|View full text |Cite
|
Sign up to set email alerts
|

Family Involvement on Efl Students’ Intercultural Communicative Competence Development During Learning From Home

Abstract: The purpose of the study is posed to diagnose the developmental stages of intercultural communicative competence during family interactions of Indonesian EFL higher education students at home context. An ethnographic approach with distant observation taken in this study due to the Covid-19 health protocol. A triangulation technique involving online interview and archival model was conducted to enhance the observation. The data collection was analyzed based on the Pyramid Model of Intercultural Competence (Dear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The lecturers commonly promoted the aspects by comparing the target culture with the students' own culture. Those teaching approaches are used to improve students' linguistic knowledge and facilitate a better oral and written skill so the students can employ various strategies in the academic situation, and that the activities carried out in the classroom contributed a lot to develop students' intercultural communicative competence (ICC) (Syam et al, 2020). The literature review revealed a relationship between intercultural communicative competence and EAP studies, with students having higher levels of intercultural communicative competence also having higher levels of academic success (Douglas & Rosvold, 2018).…”
Section: Edimentioning
confidence: 99%
“…The lecturers commonly promoted the aspects by comparing the target culture with the students' own culture. Those teaching approaches are used to improve students' linguistic knowledge and facilitate a better oral and written skill so the students can employ various strategies in the academic situation, and that the activities carried out in the classroom contributed a lot to develop students' intercultural communicative competence (ICC) (Syam et al, 2020). The literature review revealed a relationship between intercultural communicative competence and EAP studies, with students having higher levels of intercultural communicative competence also having higher levels of academic success (Douglas & Rosvold, 2018).…”
Section: Edimentioning
confidence: 99%